2002
DOI: 10.1359/jbmr.2002.17.2.284
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dynamic Axial Loading on the Rat Growth Plate

Abstract: Longitudinal bone growth can be suppressed by compressive loading. In this study, we applied three different magnitudes (17, 8.5, and 4N) of compressive force to growing rat ulnas 10 minutes/day for 8 days and investigated the effects on the distal growth plate biology. Further, to investigate growth rate recovery after cessation of loading, we examined rats 7 days after the loading period. Longitudinal growth of the ulna was suppressed in a dose-dependent manner by applied compressive force. In the 17N group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 38 publications
9
87
5
Order By: Relevance
“…A much smaller effect on growth occurs with cyclic loading. 8,15,16 Recent evidence 22 suggests that endochondral growth varies acutely and correlates inversely with activity level, but that over time the growth is relatively insensitive to cyclic loading. This differs from the The age is that of the animals at the time of growth measurement after administration of the second fluorochrome, that is 7 days after installation of the loading apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A much smaller effect on growth occurs with cyclic loading. 8,15,16 Recent evidence 22 suggests that endochondral growth varies acutely and correlates inversely with activity level, but that over time the growth is relatively insensitive to cyclic loading. This differs from the The age is that of the animals at the time of growth measurement after administration of the second fluorochrome, that is 7 days after installation of the loading apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Growth plates appear to be affected less by cyclic stress than by sustained stress. 8,15,16 The primary aim of this study was to document the alteration of growth at two different anatomical growth plate locations, for three differing levels of sustained stress, in three different species, and for animals of differing ages. The secondary aim was to identify differences between the growth response to stress between species, anatomical location, and underlying growth rate that might help determine the likely growth-stress relationship in human growth plates.…”
Section: Introductionmentioning
confidence: 99%
“…13 Experimental data have shown that cyclic forces applied to growth plates in the growing skeleton induce cellular proliferation, differentiation, matrix biosynthesis, as well as growth arrest under extreme loading. [15][16][17][18][19] However, whether chondral development is regulated by mechanical stresses in fetal or postnatal development is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in body height is, in some part, due to the increase of intervertebral disc height [21]. However, numerous reports have shown inconsistent effects of weightlessness or unloading on longitudinal bone growth: it can inhibit bone formation [18], have no effect at all on bone size [18], or suppress bone enlargement [20,24,28,30,32]. The reported effects of excess loading, as in the case of competitive athletes, are also contradictory, showing induction or reduction of longitudinal growth, most likely due to variations in the type and rate of the physical activity [4,15,27].…”
Section: Introductionmentioning
confidence: 99%